The prevalence and related factors of compassion fatigue among nursing interns: a cross-sectional study - Liqin Ye; Xianping Tang; Yanyang Li; Yutong Zhu; Jiaxin Shen; Ying Zhu; Fang Fang (BMC, 2024)
Abstract Background Compassion fatigue is common among nurses and can lead to decreased motivation, impaired physical and mental health, and turnover. Nursing interns often face environments the same as professional nurses, yet their compassion fatigue has received less attention. Therefore, this study aims to assess the prevalence and related factors of compassion fatigue among nursing interns. Methods This was a cross-sectional study involving 221 nursing interns in 2 tertiary-level hospitals in Shanghai, China. A general information questionnaire was formulated to investigate the demographic characteristics and internship-related factors of nursing interns. Compassion fatigue was assessed using the Professional Quality of Life Scale [compassion satisfaction (CS), burnout (BO), and secondary traumatic stress (STS)]. Psychological resilience, empathy, and perceived stress were evaluated by the Connor-Davidson Resilience Scale, Jefferson Scales of Empathy, and Perceived Stress Scale, respectively. Personality traits were assessed using the extroversion/introversion subscale of the Eysenck Personality Inventory. Descriptive statistics, t-test, one-way analysis of variance (ANOVA), Pearson's correlation analysis, and multiple linear regressions were used to determine the predictors of the main research variables. Results The prevalence of mild, moderate, and severe compassion fatigue in 221 nursing interns (mean age 21 years, 202 [91.4%] females) was 10.4%, 46.6%, and 43.0%, respectively, and their mean scores for CS, BO, and STS were 29.75 ± 6.39, 28.72 ± 4.78, and 28.51 ± 7.51, respectively. Psychological resilience and empathy were the strongest protective factors for CS and BO, respectively (p < 0.001), and the number of night shifts monthly was the most significant positive independent predictor of STS (p = 0.001). Additionally, male gender negatively predicted CS (p = 0.009). Younger age and extended daily working hours were associated with elevated levels of both BO and STS (p < 0.05). Clinical nursing teachers with intermediate or senior titles, as well as departments of pediatrics and obstetrics had a positive effect on STS (p < 0.05), while internship time had a negative effect on STS (p = 0.005). Furthermore, the variables of perceived stress, personality traits, and choice of nursing profession did not exhibit statistical significance in the multivariate analysis. Related factors predicted 14.2%, 26.2%, and 23.9% of the variance in the model of CS, BO and STS, respectively (all P < 0.001). Conclusion The compassion fatigue of nursing interns was more serious, especially for nursing interns who were male and younger, and who had shorter internship time, departments of pediatrics and obstetrics, and clinical nursing teachers with intermediate or senior titles. Nursing educators can improve the psychological resilience and empathy of nursing interns by offering relevant psychological courses according to the different stages of internship, as well as rationalizing their daily working hours and the frequency of night shifts to improve the compassion fatigue of nursing interns. Registration Number ChiCTR2400081968.